Investigating the Visual Privacy of House Layouts in Negeri Sembilan Traditional Malay Houses - Syazwani Zamri; Noor Hayati Ismail; Azhani Abd Manaf (Penerbit UiTM, 2024)
Vol.10.No.2 (2023) page: 65-80